Anxiety and fear about childbirth and postpartum period in last trimester and its relation to childbirth pain - Meltem Uğurlu; Tülay Yavan (Perinatal Medicine Foundation, 2022)
Objective: This study aimed to determine the fear and anxiety related to childbirth and postpartum period in last trimester for pregnant women, and its relation to childbirth pain. Methods: This study was conducted in a training and research hospital's obstetric clinic in Turkey. Totally, 104 pregnant women admitted to the hospital during the last trimester and they were followed up to delivery, which occurred in the same hospital. Data were gathered with an Information Form, Fear of Childbirth and Postpartum Anxiety Scale (FCPAS), Spielberger State and Trait Anxiety Inventory (STAI) and Visual Analogue Scale (VAS). Results: The mean FCPAS score of the women was 4.87±1.25. The highest scores were for the FCPAS subscales of fears about breastfeeding, behavior of the health staff at childbirth, and the possibility of Cesarean section. Labor pain had a significant positive weak relation with fear about childbirth and the total STAI-State score (r=0.281, p=0.041; r=0.327, p=0.017), respectively. Conclusion: It is important to determine the fear and anxieties about childbirth and postpartum period experienced during last trimester, in terms of planning prenatal education and counseling services, and supporting women to cope effectively.